2022
DOI: 10.1097/sla.0000000000005694
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Rates of Surgery and Postoperative Mortality Among Patients Receiving Chronic Kidney Replacement Therapy

Abstract: Objective: To estimate the incidence and postoperative mortality rates of surgery, and variations by age, diabetes, kidney replacement therapy (KRT) modality, and time over a 15-year period. Background: Patients with kidney failure receiving chronic KRT (dialysis or kidney transplantation) have increased risks of postoperative mortality and morbidity. Contemporary data on the incidence and types of surgery these patients undergo are lacking. Methods: This binational population cohort study evaluated all incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
(81 reference statements)
0
6
0
Order By: Relevance
“…A systematic review of literature has demonstrated that bariatric surgery in ESKD patients has similar post-operative weight loss to that of the general population; 6 however, it is associated with increased peri-operative mortality and cardiac events. 7 The annual cost of dialysis is estimated at NZ$115,712. Sleeve gastrectomy and related follow-ups are estimated to cost $23,000, while the first year's costs of transplantation is $107,361 but then reduces to $10,000-$15,000 annually from the clinical correspondence 101 second year onwards.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of literature has demonstrated that bariatric surgery in ESKD patients has similar post-operative weight loss to that of the general population; 6 however, it is associated with increased peri-operative mortality and cardiac events. 7 The annual cost of dialysis is estimated at NZ$115,712. Sleeve gastrectomy and related follow-ups are estimated to cost $23,000, while the first year's costs of transplantation is $107,361 but then reduces to $10,000-$15,000 annually from the clinical correspondence 101 second year onwards.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the overall rates of surgery in patients on chronic KRT were up to 6 times higher than in the general population, even when compared with patients with earlier stages of chronic kidney disease. 4,10,17 However, these studies were limited by size, jurisdictional breadth, procedural scope, and inadequate characterization of KRT characteristics, and did not suggest potential reasons for patients undergoing certain types of surgery or developing surgical disease in the first place. Nor did they assist in identifying modifiable preoperative risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…P atients with kidney failure on chronic kidney replacement therapy (KRT) have higher rates of surgery compared with the general population, as well as higher odds of postoperative mortality and morbidity following all types of surgery. [1][2][3][4][5] Kidney failure refers to patients with abnormal kidney function requiring either chronic dialysis or having a kidney transplant with the intention to treat them long-term. 6 The prevalence of kidney failure is expected to double by 2030 worldwide, and as such, an increasing number of patients with kidney failure will likely contemplate surgery.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations